CITRA IBU DALAM LIRIK LAGU KOREA: KAJIAN KRITIK SASTRA FEMINIS - , PUTU THENISYA PURNAMITHA, Suray Agung Nugroho S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is analyzing about mothersâ image in Korean song lyrics using feminist literary critics. Those lyrics are âìë§â [Eomma] by a male solo Ra. D (2010), âìë§â [Eomma] by boy band INFINITE (2013), âDear Momâ by ìëìë [SoNyeoShiDae] or Girlsâ Generation (2009), âì´ë¨¸ëê»â [Eomeonimkke] by boyband G.O.D (1999), âì´ë¨¸ëâ [Eomeoni] by a hip-hop group 1TYM (2001), âMotherâ by an indie band named Standing Egg (2012) and last, âìë§ ë¸ì´ëê¹ìâ [Eomma Ttalinikkayo] by a female solo ë°ê¸°ì [Park Gi Young]. The reason for using mother themed song lyrics as material object is to understand the Korean peoples thought of mothersâ figure from the popular literature perspective. The purposes of this research are to be able to do analyzing of meaning of song lyrics by applying Riffaterre semiotics theory with heuristic and hermeneutic reading method. Besides that, another purpose are able to analyze the mothersâ image that exists in the lyrics that used as material object in this research, and be able to specify the feminist ideas that exist in the mother themed lyrics. The theories that used in this research are Riffaterre semiotic theory and feminist literary critics. The conclusion that gained after analyzing, mothersâ role that being portrayed in the lyrics are a mother that giving an unconditional love and for her children, a caring mother, the struggling of a mother for her childrenâs happiness, protect, educate, and guide her children to the right path. The feminist ideas that exist in the lyrics is a mothersâ ability to working outside the domestic place to support her family. On the âì´ë¨¸ëê»â [Eomeonimkke] lyrics sung by G.O.D, the mother that portrayed on this lyrics is a pro-feminist because she did a job to support her family, that usually a menâs job or a fathersâ obligation. Keywords: Mothersâ image, song lyrics, feminist literary critics, feminism